CYTOTOXIC ACTIVITY OF COMBINED FIG EXTRACT AND OLIVE OIL AGAINST BREAST CANCER CELLS - Naniek Widyaningrum; Atina Hussana; Reza Saeful Adi; Memi Tiastuti; Karina Misti Utami (Universitas Muhammadiyah Magelang, 2020)
Figs and olive oil are plants containing flavonoids compounds. Flavonoids have antioxidant and cytotoxic activities. This study aims to find out the antioxidant and cytotoxic activities of fig extract, olive oil and combination of fig and olive oil as well. Study using a combination of tin and olive oil with a combination of extracts of 1: 0.1: 3, 1: 1, 3: 1, 0: 1. Cytotoxic and antioxidant activities were tested using MTT assay and DPPH method. Cytotoxic test results were analyzed using probit and antioxidant tests using linear regression. Test results from a single olive on T-47D cells have very strong cytotoxic and antioxidant activities (560,769 and 33.27 µg / ml). In MCF-7 cells the ratio of figs and olives 1: 1 has very strong antioxidant and cytotoxic activity (576,459 and 76.79 µg / ml), in 4T1 cells the ratio of fruitbtin and olive combination of 3: 1 has no cytotoxic activity but has antioxidant activity very strong (1733,517 and 21.81 µg / ml). The combination of fig extract and olive oil had cytotoxic activity on T-47D and MCF-7 cells, but did not have cytotoxic activity on 4T1 cells. This combination had very strong antioxidant activity in T-47D and 4T1 cells, strong in MCF-7 cells.